The Role of Ultrasound as an Adjunct to Arterial Catheterization in Critically Ill Surgical and Intensive Care Unit Patients. Issue 1 (January 2014) - Zochios, Vasileios A.; Wilkinson, Jonathan; Dasgupta, Kausik
Objective: To review the evidence behind Ultrasound (US) guided placement of arterial cannulae and its use in the critically ill population. Data sources: We performed a computer-aided literature search using set search terms and electronic data bases of PubMed and EMBASE from their commencement date through the end of July 2013. Summary of review: Insertion of intra-arterial catheters is a commonly performed invasive procedure in the peri-operative and intensive care setting that facilitates invasive blood pressure and cardiac output monitoring as well as frequent blood sampling. Arterial catheterization can be particularly challenging in critically ill and high-risk surgical patients with circulatory collapse, low cardiac output state and peripheral edema, all of which can limit the ability to successfully palpate and cannulate the artery. There is a convincing body of evidence suggesting a decrease in complication rate and first-pass success rate in US guided central venous catheter (CVC) insertion compared with the landmark technique. While most intensivists and peri-operative physicians are familiar with US guided CVC placement, fewer use US to guide arterial access. Conclusions: Most studies have demonstrated a higher success rate when using US guidance for arterial cannulation. Moreover, the technique permits more rapid access and establishment compared with the conventional palpation technique. However, there is evidence opposing the routine use of US to guide arterial cannula insertion. Further studies are required to ascertain the benefits and cost effectiveness of US guided arterial catheterization in peri-operative and critical care.